2017
DOI: 10.37358/rc.17.9.5833
|View full text |Cite
|
Sign up to set email alerts
|

Determining Visfatin / NAMPT Serum Levels by ELISA Technique, in Pregant Women with Preeclampsia

Abstract: Fig. 1.Sirtuin enzymatic activities: Sirtuins are NAD + -dependent deacetylases and mono-ADP-ribosyltransferases that regulate a wide array of proteins involved in metabolism and cell survival.The α-acetyl lysine residues of the target protein serve as substrates for sirtuindeacetylation, which generate 2' -OAADPr as a by-product. NAM, nicotinamide [8]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Hypertension does not seem to alter visfatin plasma levels. Our study, conducted on two different types of hypertensive patients, also confirms these findings [ 18 ].…”
Section: Adipokines As Biomarkers In Atherosclerotic Heart Diseasesupporting
confidence: 88%
“…Hypertension does not seem to alter visfatin plasma levels. Our study, conducted on two different types of hypertensive patients, also confirms these findings [ 18 ].…”
Section: Adipokines As Biomarkers In Atherosclerotic Heart Diseasesupporting
confidence: 88%
“…Leptin is a proatherogenic adipokine, which is excessively secreted in obese patients, together with other adipokines with similar effects, such as resisitin [20] or visfatin [21]. Overweight and obese patients with heart failure are hyperleptinemic.…”
Section: Resultsmentioning
confidence: 99%
“…Preeclampsia, a systemic vascular disease, may affect various organs, leading to severe complications of the fetus and of the pregnant mother. Even if precise causes that determine preeclampsia are not yet established, several studies have shown, that placental dysfunctions play an important role in the emergence of this disease, being correlated to the subsequent maternal endothelial disfunctions [1,2]. The anatomical presentation of placenta in case of pregnant women suffering from severe preeclampsia has frequently shown the presence of infarcts, fibrinoid necrosis of the blood vessels walls, thrombosis and signs of chronic inflammation [1,3].…”
Section: Gestational Hypertensionmentioning
confidence: 99%